Strategi Metode Pembelajaran dalam Rangka Meningkatkan Mutu Santri di TPQ Hidayatul Mubtadi’in Desa Sukorejo Kecamatan Udanawu Kabupaten Blitar - Mustajib (Lembaga Penelitian dan Pengabdian Masyarakat IAIN Kediri, 2022)
This research was carried out with the aim of knowing the strategy of learning methods carried out by TPQ education institution hidayatul mubtadi'in in sukorejo village, Udanawu sub-district of Blitar in improving the quality of its students, considering that TPQ education institutions are non-formal institutions that are very influential in efforts to improve the quality of students in formal institutions. The type of research used is qualitative research type, which is the type of research that examines and that can describe complex and concrete social reality. And after the research runs for several days and produces data that the researchers think is enough, then researchers can conclude that TPQ hidayatul mubtadi'in can improve the quality of santrinya by using discipline strategies, accuracy, achievement cards, support santri guardians, punishment, and awards. And of course in its implementation there must be factors that encourage or even inhibit it.